2021
DOI: 10.1016/j.redox.2021.102106
|View full text |Cite
|
Sign up to set email alerts
|

Decreased proteasomal cleavage at nitrotyrosine sites in proteins and peptides

Abstract: Removal of moderately oxidized proteins is mainly carried out by the proteasome, while highly modified proteins are no longer degradable. However, in the case of proteins modified by nitration of tyrosine residues to 3-nitrotyrosine (NO 2 Y), the role of the proteasome remains to be established. For this purpose, degradation assays and mass spectrometry analyses were performed using isolated proteasome and purified fractions of native cytochrome c (Cyt … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 9 publications
(4 citation statements)
references
References 71 publications
0
4
0
Order By: Relevance
“…Proteasomal activity was measured via a modified protocol according to 41 . Fibroblasts were cultured as described above.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Proteasomal activity was measured via a modified protocol according to 41 . Fibroblasts were cultured as described above.…”
Section: Methodsmentioning
confidence: 99%
“…Proteasomal activity was measured via a modified protocol according to. 41 Fibroblasts were cultured as described above. Both untreated control and cells after 5 days of HG-exposure were harvested by trypsination and lysed in 1 mM DTT, then passed 20 times through a 27-gauge needle attached to a 1 mL syringe, followed by centrifugation (12,000 g for 15 min at 4 C) in order to remove nonlysed cells and membrane debris.…”
Section: Measurement Of 20s I20s and 26s Proteasomal Activitiesmentioning
confidence: 99%
“…However, the data remain incomplete as the definite documentation of a bonafide denitrase, that is, an enzyme that removes the nitro group without degrading the protein, awaits confirmation. Removal of nitrated proteins by various cellular proteolytic systems has been clearly demonstrated ( 125 , 126 , 127 ). Alternatively, nitrated proteins may be removed via immunological processes.…”
Section: Updated Overview Of Protein Tyrosine Nitrationmentioning
confidence: 99%
“…NRs are polyubiquitinated ( Costa-Broseta et al, 2021 ) and are translocated to the nucleus by the SUMO E3 ligase SIZ1 ( Kim et al, 2018 ). Remarkably, a recent report showed that proteasomal-mediated cleavage at C-terminal of nitroTyr residues in proteins was reduced when compared to the unmodified residues, making nitration a possible factor that decreases the turnover of oxidized proteins ( Ott et al, 2021 ), and casting doubts on the relationship between protein nitration and proteasome-mediated degradation. However, polyubiquitination is not the only PTM functionally connected to Tyr nitration.…”
Section: Nitration Of the Enzymes Of Nitrate Assimilation And No Bios...mentioning
confidence: 99%